In vitro characterization of anodized magnesium alloy as a potential biodegradable material for biomedical applications - Moreno, Julieta; Merlo, Julieta Leticia; Renno, Ana Claudia; Canizo, Jésica Romina; Buchelly, Francisco Javier; Pastore, Juan Ignacio; Katunar, Maria Rosa; Cere, Silvia (Elsevier, 2022)
Pure metals and their alloys are used to partially or completely restore bone fractures. Biodegradable metals emerged as promising candidates for fracture fixation devices since they are able to self-degrade in the body environment. The main challenge of the devices is to reach an adequate degradation rate relative to the bone healing and also to present safe degradation by-products. Magnesium alloys are very much studied because of their promising properties, but the main limitation for their application in biomedical devices is the hydrogen evolution that results from their corrosion in aqueous media. This work assesses the effects of low potential anodizing process of AZ91 alloys in basic media on surface topography, electrochemical response, hydrogen evolution and cell attachment compared with the non-treated alloys. A comparative approach to determine the electrochemical parameters for assessing the degradation rate is also discussed. Results show that the electrochemical treatment of anodizing at low voltage in 5 mol/L KOH solution generates magnesium oxide/hydroxide on the surface which could act as a barrier to prevent fast degradation, and consequently to reduce hydrogen release. In turn, this treatment improved the adhesion of bovine embryonic fibroblasts (BEFs) and MCT3T3 pre-osteoblastic cells to the surface, showing that it could be a good candidate to be used in temporary implants.